Perceptions and Perspectives in Telepsychotherapy: Effects of Patient Severity. (Revista de Psicología, 2025)
This study explores how the severity of patients’ issues influences therapists’ perspectives on care modalities (remote or in-person) during and after the COVID-19 pandemic in La Plata, Argentina. Through a survey of 247 therapists, their experiences and opinions on telepsychotherapy, the perceived effectiveness of both modalities, and their willingness to continue with remote care were analyzed. The results showed that therapists who treated severe cases during the pandemic preferred the in-person modality and perceived greater differences in therapeutic outcomes between remote and in-person care for such cases. Additionally, the severity of patients significantly influenced the decision to return to in-person care. It is concluded that adapting mental health services to the severity of patients’ issues is essential when choosing between care modalities.
Keywords: telepsychotherapy; in-person care; severity of issues; pandemic; therapeutic effectiveness